Suicide in rural Punjab, India: implications for ensuring farmer rights - Faten Taki; Melanie Witte; Inderjit Singh Jaijee; Sonal Jessel; Elizabeth Mauer; Jacob Lurie; Gunisha Kaur (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Suicide is prevalent among farmers worldwide, and may be influenced by policies and agricultural initiatives that affect the socioeconomic insecurity. The objective of this study was to investigate the association between economic burden and suicides in rural areas of Punjab, India. # Methods Suicide data were collected using household verbal autopsy surveys by the Baba Nanak Education Society, a local non-governmental organization, from 1980 to 2016. Data from five districts were analyzed: Mansa, Sangrur, Fatehabad, Jind, Patiala. Demographic data included the date at which death by suicide occurred, age, occupation, land holding, information on the debt, and the mode of suicide, for 2,473 suicides. # Results Suicides were more prevalent among agricultural workers, which include agricultural laborers and agriculturalists (i.e. individuals involved in the business of owning agricultural land and cultivation). Agricultural workers were significantly more likely to commit suicide by poisoning, while those from other occupations preferred different means. The median age was lower in agricultural workers relative to other occupations. The frequency of suicides among agricultural workers significantly increased from 1980 to 2016. This increase was strongly correlated with the total annual debt and land holding. # Conclusions Results from this study suggest that increasing debt and land holding may significantly predispose young and middle-aged farmers to death by suicide. Policies are needed to limit the availability of hazardous chemicals that can be used as poison and to protect the economic security of farmers in Punjab and other parts of the world.